Do research universities boost regional economic development? - Evidence from China - Shuai Chu; Xiangbo Liu (Global Labor Organization (GLO), 2021)
This paper studies whether research universities can boost regional economic development through an exogenous shock of a forced relocation of a research university in China. We analyze the development in the treated regions compared with a set of control regions that are created using the synthetic control method and find that research universities can have negative effects on local economic development. We then perform a series of robustness checks. Our main results carry through. By employing a more exogenous shock and more reliable identification strategies, our study provides evidence that research universities do not necessarily promote regional economic development.
Keywords: O15; O18; R11; 330; Research Universities; Regional Economic Development; Synthetic Control Method